ZAMANAGÓY TÁLIM PROCESINDE DIDAKTIKALÍQ METODLARÍN KLASSIFIKACIYALAW - Saytbekova, S. (SCIENCE and SOCIETY, 2024)
The article gives a general concept of the term “method” and its main types, provides an analysis of the classification of teaching methods, stages of the educational process and its assimilation, a comparative analysis of methodology and technology, as well as a generalized classification of didactic teaching aids.
Keywords: method; classification; didactics; technology; educational process; teacher; student; reproductive method; programmed method; heuristic method; case-study method